Corrigendum to “A predictive model for hypocalcaemia in dairy cows utilizing behavioural sensor data combined with deep learning” [Comput. Electron. Agric. 220 (2024) 108877] (Computers and Electronics in Agriculture (2024) 220, (S0168169924002680), (10.1016/j.compag.2024.108877)) - van Leerdam, Meike; Hut, Peter R.; Liseune, Arno; Slavco, Elena; Hulsen, Jan; Hostens, Miel (Elsevier BV, 2025)
The authors regret making a textual mistake in our manuscript. Section 3.2 last sentence states: ''Rumination had limited differences between normocalcaemic and hypocalcaemic cows, except for the 5 days before calving, when the hypocalcaemic cows spent more minutes ruminating.'' The hypocalcemic cows ruminate less in the 5 day period before calving, as is visualised in the appendix. The word more should therefore be less. On top of this, the first highlight says: ''The behavioural patterns of the 21 days before calving contains valuable information for the prediction of hypocalcemia after parturition.'' Contains should be without an s, so contain to be grammatical correct. The authors would like to apologise for any inconvenience caused.
Keywords: Forestry; Agronomy and Crop Science; Computer Science Applications; Horticulture